Inhibitory effect of PGE(2) on the killing of Paracoccidioides brasiliensis by human monocytes can be reversed by cellular activation with cytokines - Bordon-Graciani, Ana Paula [UNESP]; Dias-Melicio, Luciane Alarcao [UNESP]; Acorci-Valerio, Michele Janegitz [UNESP]; Araujo, Joao Pessoa [UNESP]; Soares, Angela Maria Victoriano de Campos [UNESP] (Informa Healthcare, 2012)
Paracoccidioides brasiliensis is the etiological agent of paracoccidioidomycosis, a deep mycosis endemic in Latin America. Studies to elucidate the host-parasite relationship in this mycosis have demonstrated that non-activated phagocytes fail to kill the etiologic agent. Investigations of human monocytes have shown that the lack of fungicidal activity is partially associated with the capacity of a high-virulence strain to induce PGE(2) release by these cells. This eicosanoid inhibits production of TNF-alpha, the cytokine involved in cell activation for release of H2O2, the fungicidal metabolite. Cell priming with IFN-gamma was shown to partially reverse this inhibitory effect. In this study, we asked whether monocyte challenge with a low-virulence strain of this fungus would also result in PGE(2) release and consequently inhibition of antifungal activities. We also assessed whether PGE(2), besides inhibiting production of TNF-alpha, a monocyte-activating cytokine, also affects IL-10. The latter, in contrast to TNF-alpha, is a monocyte-suppressing cytokine. Finally, we evaluated whether priming cells with other cytokines, namely TNF-alpha and GM-CSF, could be more effective than IFN-gamma in reversing the PGE(2) inhibitory effect. The results revealed that the less virulent P. brasiliensis strain also induces human monocytes to release PGE(2). However, the inhibitory effect of PGE(2) was less pronounced when cells were challenged with this strain than with the more virulent one. It was also demonstrated that PGE(2), while inhibits TNF-alpha production, tends to increase IL-10 levels. Priming with GM-CSF or TNF-alpha was more effective than IFN-gamma in compensating for the inhibitory PGE(2) effect, since these cytokines induce cells to produce higher H2O2 and TNF-alpha levels.
Keywords: Prostaglandin E-2; cytokines; monocytes; P. brasiliensis; hydrogen peroxide